Scaling Migrant Worker Rights How Advocates Collaborate and Contest State Power - Bada, Xóchitl (University of California Press, 2023)
International migrants' home countries often play an integral part in protecting their citizens' labor and human rights abroad. At the same time, institutions such as labor unions, worker centers, and legal aid groups are among the most visible actors holding governments of immigrant destinations accountable. Focusing on Mexico and the United States, Scaling Migrant Worker Rights analyzes how these organizations pressure governments to defend migrants. The result is a multilayered picture of the impediments to migrant worker rights and the possibilities for their realization. "Highly original and timely, this book shines a light on underexplored actors in the labor rights and protection enforcement process." - LEAH F. VOSKO, author of Disrupting Deportability: Transnational Workers Organize "A very robust and nuanced empirical analysis documenting how co-enforcement mechanisms across transnational civil society, consulates, and national governments work to implement existing labor rights protections." - ALEXANDRA DÉLANO ALONSO, author of Mexico and Its Diaspora in the United States: Policies of Emigration since 1848 "This important and innovative work provides a nuanced, rich, and detailed meso-analysis of institutions and institutional collaboration in Mexico and the US." - NANCY PLANKEY-VIDELA, author of We Are in This Dance Together: Gender, Power, and Globalization at a Mexican Garment Firm